2019
DOI: 10.1161/atvbaha.118.311874
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 Promotes Vascular Smooth Muscle Cell Chondrogenic Differentiation and Consequent Calcification via the Concerted Actions of Osteoprotegerin Suppression and IL-6–Mediated RANKL Induction

Abstract: Objective— Vascular smooth muscle cell (VSMC) transformation to an osteochondrogenic phenotype is an initial step toward arterial calcification, which is highly correlated with cardiovascular disease–related morbidity and mortality. TLR2 (Toll-like receptor 2) plays a pathogenic role in the development of vascular diseases, but its regulation in calcification of arteries and VSMCs remains unclear. We postulate that TLR2-mediated inflammation participates in mediating atherosclerotic arterial calcif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(63 citation statements)
references
References 42 publications
4
55
0
Order By: Relevance
“…Notably, these NaVO 3 -induced atherosclerotic pathologies in ApoE −/− mice were prevented by NAC treatment, indicating that ROS is required for NaVO 3 -driven atherosclerosis. Our results further show that VOSO 4 and NaVO 3 promote phenotypic transitions of VSMCs from the quiescent contractile state to the active synthetic state and VSMC proliferation and migration, which has been implicated in deleterious consequences of atherosclerosis [3,25,26,29]. The present study provides experimental evidence that vanadium salts, VOSO 4 and NaVO 3 , drive VSMC pathological responses by inducing ROS production and thereby activating p38/NF-κB signaling.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Notably, these NaVO 3 -induced atherosclerotic pathologies in ApoE −/− mice were prevented by NAC treatment, indicating that ROS is required for NaVO 3 -driven atherosclerosis. Our results further show that VOSO 4 and NaVO 3 promote phenotypic transitions of VSMCs from the quiescent contractile state to the active synthetic state and VSMC proliferation and migration, which has been implicated in deleterious consequences of atherosclerosis [3,25,26,29]. The present study provides experimental evidence that vanadium salts, VOSO 4 and NaVO 3 , drive VSMC pathological responses by inducing ROS production and thereby activating p38/NF-κB signaling.…”
Section: Discussionsupporting
confidence: 72%
“…The decrease in VSMC differentiation marker proteins such as SM22α in atherosclerotic lesions is a common characteristic of atherosclerosis [3,29], we determined whether intranasal administration of NaVO 3 significantly decreased SM22α. A significant decrease in the immunopositive areas for SM22α in the atherosclerotic lesions ( Figure 1F) was found to be highly associated with enhanced neointimal formation in the atherosclerotic lesion of NaVO 3 -exposed mice ( Figure 1G).…”
Section: Intranasal Administration Of Navo 3 Induces Atherosclerosis mentioning
confidence: 99%
“…Neutrophils produce OPG and IL-17. IL-17 increases the recruitment of neutrophils at the site of inflammation and influences the production of various proinflammatory mediators [15,16]. A recent study reported a significant elevation of circulating OPG in septic patients with different levels of severity and in those who progressed to acute kidney injury; OPG thus appears to be a reliable biomarker [17].…”
Section: The Opg/rankl/rank/trail System: Structures Localizationmentioning
confidence: 99%
“…We mainly focused on the relationship between miR-34a and the prototypical pro-inflammatory SASP component IL6, which is canonically upregulated in cells that have undergone senescence, increases with age and plays a causal role in inflammaging and age-related diseases [8,30,32,33]. Besides, IL6 is one of the most abundant cytokines produced by senescent VSMCs and exerts pro-calcification activity [8,34,35]. We found that miR-34a and IL6 levels are upregulated and positively correlate in aortas of old mice and with HASMCs donors' age and senescence (Figure 1).…”
Section: Discussionmentioning
confidence: 99%